2014
DOI: 10.4172/2168-9881.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Canopys Average SPAD Readings Based on the Analysis of Digital Images

Abstract: Chlorophyll meter SPAD (Soil Plant Analysis Development) is one of the most popular tools used to monitor the N Status of rice (Oryza Sativa L.) but its high price limits it from being widely adopted. Digital imaging analysis used to detect nitrogen offers a promising, inexpensive substitute at canopy level. And the present study evaluated rice canopy SPAD readings by analyzing digital images captured with a domestic digital camera. A field experiment was conducted in 2011 using a completely randomized split-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Li et al extracted the dark green color index (DGCI) of image features, and concluded that DGCI was significantly correlated with the SPAD value of rice leaves. Thus, DGCI could be used to estimate the chlorophyll value of rice leaves and indirectly evaluate the growth and nutrition status of rice [17]. Jia et al used a digital camera and a Greenseeker hand-held sensor to monitor cotton growth and N status.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al extracted the dark green color index (DGCI) of image features, and concluded that DGCI was significantly correlated with the SPAD value of rice leaves. Thus, DGCI could be used to estimate the chlorophyll value of rice leaves and indirectly evaluate the growth and nutrition status of rice [17]. Jia et al used a digital camera and a Greenseeker hand-held sensor to monitor cotton growth and N status.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al extracted the dark green color index (DGCI) of image features, and concluded that DGCI was significantly correlated with the SPAD value of rice leaves. Thus, DGCI could be used to estimate the chlorophyll value of rice leaves and indirectly evaluate the growth and nutrition status of rice [18]. Jia et al used a digital camera and a Greenseeker hand-held sensor to monitor cotton growth and N status [19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional destructive spectroscopic methods of Chl estimation (Lichtenthaler and Wellburn 1983), sensor-based, modern, noninvasive approaches have received considerable attention due to their highthroughput and real-time measurement abilities (Cassol et al 2008, Yadav et al 2010, Rigon et al 2012, Stefan et al 2013, Jinwen 2014, Novichonok et al 2016. Different types of Chl meters (Pagola et al 2009, Novichonok et al 2016, multi-spectral (Reyniers et al 2006) and hyper-spectral sensors (Chen et al 2010, Li et al 2014 have been developed to measure absorbance and spectral reflectance of leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of Chl meters (Pagola et al 2009, Novichonok et al 2016, multi-spectral (Reyniers et al 2006) and hyper-spectral sensors (Chen et al 2010, Li et al 2014 have been developed to measure absorbance and spectral reflectance of leaves. Among Chl meters, the SPAD meter (SPAD-502, Minolta, Japan) has been widely used to measure the Chl content as well as to assess crop nitrogen status nondestructively (Uddling et al 2007, Cabangon et al 2011, Ling et al 2011, Liu et al 2012, Wang et al 2013, 2014Yuan et al 2016, Vesali et al 2017, Agarwal and Dutta Gupta 2018. The instrument measures transmission of light absorbed by Chl in the red band (650 nm), as well as transmission of infrared light (950 nm), where no absorption of Chl occurs.…”
Section: Introductionmentioning
confidence: 99%